2019
DOI: 10.1194/jlr.p094375
|View full text |Cite
|
Sign up to set email alerts
|

Four nights of sleep restriction suppress the postprandial lipemic response and decrease satiety

Abstract: Supplementary key words triglycerides • nutrition • lipolysis and fatty acid metabolism • diet and dietary lipids • fatty acid • insulin resistance • inflammation • hormones • glucose According to the Centers for Disease Control and Prevention, one in three US adults sleeps fewer than 7 h per night, increasing their risk of obesity and for risk of developing CVD, type 2 diabetes, and earlier mortality, among other comorbidities (1-4). The mechanisms by which chronic insufficient sleep increases cardiometabolic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 80 publications
0
23
0
Order By: Relevance
“…Participants consumed three meals per day (breakfast at 09:05, lunch at 12:05, and dinner at 18:05). Meals did not contain caffeine or alcohol (see Ness et al 51 for further details).…”
Section: Methodsmentioning
confidence: 99%
“…Participants consumed three meals per day (breakfast at 09:05, lunch at 12:05, and dinner at 18:05). Meals did not contain caffeine or alcohol (see Ness et al 51 for further details).…”
Section: Methodsmentioning
confidence: 99%
“…For example, the current study assessed Adipo-IR after one night of total sleep deprivation. In contrast, results from human studies suggest chronic partial sleep loss impairs adipose tissue function as indicated by impaired insulin signalling [5], increased nocturnal NEFA [4] and impaired NEFA rebound [27]. Therefore, a longer duration of insufficient sleep may be necessary to induce alterations in Adipo-IR.…”
Section: Discussionmentioning
confidence: 94%
“…As discussed above in relation to weight loss studies, it is important to be cautious when interpreting studies that did not employ a control group. Two studies of sleep deprivation were reported (5 h vs. 10 h of ‘time in bed’ per night) using data from the same study participants [ 106 , 107 ]; participants were studied before, during, and after this reduction in sleep to 5 h per night, yet no control group was studied over the same timeframe. In one of these studies, plasma FFA concentration was surprisingly reduced after four nights of sleep restriction and remained reduced below baseline after restoration of sleeping patterns [ 107 ].…”
Section: Modulation Of Plasma Ffa Concentration By Clinical Interventions and Lifestyle Factorsmentioning
confidence: 99%